A quantitative analysis of the polyamine in lung cancer patient fingernails by LC‐ESI‐MS/MS. (9th October 2013) - Min, Jun Zhe; Matsumoto, Akihito; Li, Gao; Jiang, Ying‐Zi; Yu, Hai‐fu; Todoroki, Kenichiro; Inoue, Koichi; Toyo'oka, Toshimasa
ABSTRACT A quantitative analysis of polyamines in lung cancer patient fingernails by the combination of 4‐(N, N‐dimethylaminosulfonyl)‐7‐fluoro‐2, 1, 3‐benzoxadiazole derivatives and liquid chromatography–electrospray ionization tandem mass spectrometry is described. The reaction of the reagent with eight kinds of polyamines, that is, N1‐acetylputrescine (N1‐actPUT), N8‐acetylspermidine, N1‐acetylspermine, 1, 3‐diaminopropane, putrescine (PUT), cadaverine, spermidine and spermine (SPM) effectively occurs at 60 °C for 30 min. The detection limits (signal‐to‐noise ratio 5) were 5–100 fmol. A good linearity was achieved from the calibration curves, which was obtained by plotting the peak area ratios of the analytes relative to the internal standard (IS), that is, 1, 6‐diaminohexane, vs the injected amounts of polyamines (r2 > 0.996), and the intra‐day and inter‐day assay precisions were <9.84%. Furthermore, the recoveries (%) of the polyamines spiked in the human fingernails were 89.14–110.64. The present method was applied to human fingernail samples from 17 lung cancer patients and 39 healthy volunteers. The polyamine concentration was different based on the gender, that is, the N1‐actPUT and PUT contents were 3.10 times and 2.56 times higher in healthy men than in women, respectively. Additionally, in the lung cancer patient group, as compared with the healthy volunteers, the concentrations of SPM had a statistically significant (p < 0.05) correlation. Therefore, because the proposed method provides a good mass accuracy and the trace detection of the polyamines in human fingernails, this analytical technique could be a noninvasive technique to assist in the diagnosis and assessment of disease activity in lung cancer patients. Copyright © 2013 John Wiley & Sons, Ltd.